2010
DOI: 10.1002/chem.200901209
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transferrin in Actinide(IV) Uptake: Comparison with Iron(III)

Abstract: The impact of actinides on living organisms has been the subject of numerous studies since the 1950s. From a general point of view, these studies show that actinides are chemical poisons as well as radiological hazards. Actinides in plasma are assumed to be mainly complexed to transferrin, the iron carrier protein. This paper casts light on the uptake of actinides(IV) (thorium, neptunium, plutonium) by transferrin, focusing on the pH dependence of the interaction and on a molecular description of the cation bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 98 publications
2
41
0
Order By: Relevance
“…Plutonium can bind transferrin and enter mammalian cells via the ferric transferrin uptake machinery. 167 The interplay between plutonium and microorganisms has also been investigated. Desferrioxamine (DFO) siderophores display high affinity for Pu(IV); 168 for Pu(IV)-DFOB, log β 110 = 30.8 and Pu(IV)-DFOE is sufficiently stable that its crystal structure was determined using X-ray diffraction methods (Figure 5).…”
Section: Other Metals: Transport and Sequestrationmentioning
confidence: 99%
“…Plutonium can bind transferrin and enter mammalian cells via the ferric transferrin uptake machinery. 167 The interplay between plutonium and microorganisms has also been investigated. Desferrioxamine (DFO) siderophores display high affinity for Pu(IV); 168 for Pu(IV)-DFOB, log β 110 = 30.8 and Pu(IV)-DFOE is sufficiently stable that its crystal structure was determined using X-ray diffraction methods (Figure 5).…”
Section: Other Metals: Transport and Sequestrationmentioning
confidence: 99%
“…Although they are known to rapidly circulate and deposit into major organs such as bone, liver, or kidney after contamination (6,(8)(9)(10), the specific molecular mechanisms associated with mammalian uptake of these toxic heavy elements remain largely unexplored. Proposed mammalian actinide acquisition and transport mechanisms have typically focused on proteins that use conserved motifs to directly bind the essential elements iron or calcium (6,8,(10)(11)(12)(13), such as transferrin (14)(15)(16)(17)(18), ferritin (13), osteopontin (19), or fetuin (20). Siderocalin (Scn), an essential antibacterial protein that sequesters iron (21,22), and an important component of iron trafficking (23), is distinct in that it binds ferric iron indirectly, through tight complexes with a siderophore or siderophore-derived chelator.…”
mentioning
confidence: 99%
“…The increase of complexation can be relatively well reproduced till a carbonate concentration of 10 [28,31]. It is worth saying that the absence of complexation between Th(IV) and transferrin observed by Jeanson et al [15] is certainly due to a kinetic problem; Th and HSTf were contacted only for a few hours. Several parameters may explain these differences between Th(IV) and Fe(III) binding.…”
Section: +4mentioning
confidence: 74%
“…Furthermore, one recent study showed no interaction between Th(IV) and HSTf [15], these results being rather conflicting with the others.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation